2021
DOI: 10.1038/s41598-021-81281-w
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and characterization of gold nanoparticles using Brazilian red propolis and evaluation of its antimicrobial and anticancer activities

Abstract: Gold nanoparticles (AuNPs) are highlighted due to their low toxicity, compatibility with the human body, high surface area to volume ratio, and surfaces that can be easily modified with ligands. Biosynthesis of AuNPs using plant extract is considered a simple, low-cost, and eco-friendly approach. Brazilian Red Propolis (BRP), a product of bees, exhibits anti-inflammatory, anti-tumor, antioxidant, and antimicrobial activities. Here, we described the biosynthesis of AuNPs using BRP extract (AuNPextract) and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 98 publications
6
94
0
6
Order By: Relevance
“…3 International Journal of Polymer Science For Pro (Figure 1-Pro), 889 cm-1 (C-H bonds of phenolic rings), 1151 and 1282 cm-1 (stretched C-O and C-N bond of amino acids aromatic), 1621 cm-1 (-COO − carboxylate anion), 1654 and 2971 cm-1 (C=O of flavonoids), 2924 cm-1 (stretched CH 2 vibrations of phenolics), and broadband around 3432 cm-1 (Free N-H) [33,39,40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 International Journal of Polymer Science For Pro (Figure 1-Pro), 889 cm-1 (C-H bonds of phenolic rings), 1151 and 1282 cm-1 (stretched C-O and C-N bond of amino acids aromatic), 1621 cm-1 (-COO − carboxylate anion), 1654 and 2971 cm-1 (C=O of flavonoids), 2924 cm-1 (stretched CH 2 vibrations of phenolics), and broadband around 3432 cm-1 (Free N-H) [33,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Pro exhibited numerous bioactive compounds and bioactivities and was effectually employed in plentiful pharmacological and biomedical applications [27], including its powerful antimicrobial action, inflammatory, antioxidant, and wound healing potentiality [28][29][30]. The bee Pro could efficiently synthesize metals' NPs (e.g., silver, gold, and selenium), stimulated by Pro content from biomolecules like flavonoids, alkaloids, phenols, terpenoids, and steroids [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Artepillin C and p-coumaric acid are two of the major compounds that contribute to these activities [ 33 ]. Brazilian red propolis extract has a cytotoxic effect against colon cancer cell lines, bladder cancer cells (T24), and prostate cancer cells (PC-3) [ 23 , 78 , 79 ]. DMEM extracts of Turkish propolis exerts cytotoxic effects on MDA-MB-231 cells [ 80 ].…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
“…Apoptosis induction by propolis and its compounds coming from different geographical regions has been proven in many studies [ 19 , 55 , 59 , 61 , 67 , 79 , 82 , 87 , 88 , 89 , 90 , 91 , 92 ], while in this review, we want to focus strictly on the demonstrated molecular mechanisms of this process.…”
Section: Mechanisms Of Anticancer Activity Of Propolis and Its Compoundsmentioning
confidence: 99%
“…Rajasekharreddy et al [14] In the present study, the Au NPs were prepared by green synthesis, where the plant extracts of D. uncinatum and E. guineense were used as a reducing agent. Green synthesized Au NPs are reported for antibacterial [15,16], antioxidant [17], anticancer [18] etc. but to the best of our knowledge it is not used in Alzeimer disease.…”
Section: Introductionmentioning
confidence: 99%